Physical, functional and biochemical features of Nanoskin® bacterial cellulose scaffold as a potential carrier for cell transference - Viveiros, Magda Massae Hata [UNESP]; Rainho, Cláudia Aparecida [UNESP]; Ramirez, Jofer Andree Zamame [UNESP]; Kaneno, Ramon [UNESP]; Silva, Márcia Guimarães [UNESP]; Ximenes, Valdecir Farias [UNESP]; de Olyveira, Gabriel Molina; Basmaji, Pierre; Di Girolamo, Nick; Schellini, Silvana Artioli [UNESP] (Elsevier, 2022)
We evaluated the feasibility of Nanoskin®, a bacterial cellulose (BC) nanofiber membrane, as a potential scaffold for cell transference therapy. Nanoskin® does not induce lymphocyte proliferation, but it does not kill lymphocytes. Human mesenchymal stem cells (MSCs) and lymphocytes produced significantly elevated amounts of interleukin (IL)-10 (p = 0.0005; p = 0.02) when in contact with Nanoskin®. In conclusion, the Nanoskin® can be a promising biomaterial for use as a cell carrier-scaffold in cell transference therapies.
Keywords: Bacterial cellulose; Cell transference; Nanoskin®; Regenerative medicine; Scaffold